Mechanisms of an electron stream self-bunching in magnetron guns - Gritsunov, A.V. (Вопросы атомной науки и техники, 2004)
Various processes of self-bunching of reentrant electron cloud nearby a distributed cylindrical cathode in crossed
fields are investigated theoretically using particle-in-cell (PIC) simulation algorithms. As most probable mecha
nisms of formation of an azimuthally heterogeneous electron beam, tangential eigenmodes (i.e., natural tangential
oscillations) of the electron cloud, secondary-emission bunching of one and true solitons generation in the beam are
considered and compared. Illustrations of all just listed bunches as well as of some other turbulence phenomena at
the electron hub are given, and their possible influence on the magnetron guns performance is discussed. Теоретично досліджено процеси самогрупування замкненої електронної хмари поблизу розподіленого
циліндричного катода в схрещених полях. Найбільш ймовірними механізмами групування є власні
тангенційні коливання, вторично-емісійні згустки та справжні солітони. Теоретически исследованы процессы самогруппировки замкнутого электронного облака вблизи распределенного цилиндрического катода в скрещенных полях. Наиболее вероятными механизмами группировки
являются собственные тангенциальные колебания, вторично-эмиссионные сгустки и истинные солитоны.